An examination of blameworthiness on the federal sentencing of organizations to implement corporate compliance programs. Issue 2 (3rd April 2022) - Homer, Emily M.; Higgins, George E.
ABSTRACT: In federal courts in the U.S., judges can require criminal organizations to implement corporate compliance programs, ideally to decrease future crime occurrences. However, it is unclear of the circumstances that merit this sentence. This study examines a primary consideration when sentencing criminal organizations that is drawn from the focal concerns framework: the blameworthiness of the organization in the commission of the crime. The study uses data compiled by the U.S. Sentencing Commission from federal documents for 1, 125 organizations that were sentenced in federal criminal courts between October 1, 2010, and September 30, 2017. Results showed that several measures of blameworthiness were significantly related to the sentencing of corporate compliance programs, showing partial support for the focal concern of blameworthiness. The policy implications of these findings are also discussed.